Evaluasi Usability dan Rekomendasi Perbaikan User Interface pada Aplikasi Mobile Cinepolis Indonesia menggunakan Metode Usability Testing - Handita Anya Prameswari; Yusi Tyroni Mursityo; Hanifah Muslimah Az-zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In this era of globalization, there's a fierce competition for big company to gives their customers the best service. Cinepolis Indonesia provides an app that is useful for ordering movie ticket via Internet with the tagline of â€œMudah, Aman, Nyamanâ€ (â€œEasy, Secure, Convenienceâ€). But according to the observation and the reviews from customers, there are several user interface problems, such as the repeating usage of sorting algorithm, no feature to watch movie trailer directly from the app, and some elements that doesn't fit well to the app. Therefore, a research on its usability level is needed. There are four usability aspects that will be researched. Learnability, Efficiency, Errors aspects are going to be researched using Usability Testing methods, while Satisfaction aspect will be researched using LEMTool - Measuring Emotions in Visual Interfaces. After the first evaluation, 16 problems was found from the 8 task scenarios that was tested. Then, after the user interface design improvements based on Apple Human Interface Guidelines and the second evaluation, its usability metric results are compared. The Learnability aspects had an increase of 19%, from 77% on the first evaluation into 96,1% on the second evaluation. The Efficiency aspects had an increase of 3%, from 8% on the first evaluation to 11% on the second evaluation. The Errors aspects had a significant decrease of 19%, from 21% on the first evaluation to 2% on the second evaluation. Lastly, the Satisfaction aspects had an increase of 29,89%, from 69% on the first evaluation to 98,89% on the second evaluation. In conclusion, the design result of user interface improvements has a better usability value when compared to the user interface design of Cinepolis Indonesia application before improvements are made.